Influence of the Near-Cortical Over-Drilling Technique on the Mechanical Behaviour of Locking Plate Constructs Applied in Maned Wolf's Femur - Siqueira, Rafael C.; Rahal, Sheila C.; Mesquita, Luciana R.; Voorwald, Fabiana A.; Fernandes, Martin F.; Tosati, Marcos; Ribeiro, Celso R.; Scorsato, Paulo S. (Veterinary and Comparative Orthopaedics and Traumatology, 2022)
Objective The aim of this study was to evaluate the influence of near-cortical over-drilling holes on the mechanical behaviour of locking plate constructs applied in maned wolf's femur by using mechanical testing and finite element method (FEM).Study Design Seven pairs of adult maned wolves (Chrysocyon brachyurus) femur bones were randomly distributed into four groups. In all groups, a 3.5 mm locking compression plate, designed with 12 combi-holes and one locked, was applied to the lateral surface of the femur. G1 (n = 4) received bicortical locking screws placed in holes 1, 3, 5, 8, 10 and 12. In G2 (n = 5), the plate was applied as used in G1, but the application of the locked screws involved the near-cortical over-drilling technique. In G3 (n = 4), the plate was applied as used in G2, but the size of the near-cortical over-drilling was larger. The combi-holes 6 and 7 were maintained over a 10 mm fracture gap without screws. All constructs were tested for failure in the axial load. The axial load was applied eccentrically to the femoral head.Results Statistical differences were observed in the maximum load with G3 > G1 and G3 > G2, and in the deflection with G2 > G1 and G2 > G3. The FEM showed the lowest total displacement of the bone-plate constructs as well as of the plate in G1 compared with G2 and G3.Conclusion The near-cortical over-drilling technique used in unstable fractures induced in the maned wolf's femur showed by static axial compression test that maximum load and deflection are dependent on drill hole size induced in the near-cortex. Based on FEM, the lowest total displacement of the bone-plate constructs was observed in Group 1.
Keywords: locked plate; near-cortex overdrilling; fracture; canid; finite element method